2022
DOI: 10.1117/1.nph.9.1.015001
|View full text |Cite
|
Sign up to set email alerts
|

Reducing false discoveries in resting-state functional connectivity using short channel correction: an fNIRS study

Abstract: . Significance: Functional near-infrared spectroscopy (fNIRS) is a neuroimaging tool that can measure resting-state functional connectivity; however, non-neuronal components present in fNIRS signals introduce false discoveries in connectivity, which can impact interpretation of functional networks. Aim: We investigated the effect of short channel correction on resting-state connectivity by removing non-neuronal signals from fNIRS long channel data. We hypothesize… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
14
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 40 publications
1
14
0
Order By: Relevance
“…First, this approach attempts to address the issue of spurious correlations in functional connectivity measures introduced by systemic physiological artifacts (particularly due to Mayer waves around 0.05-0.1 Hz). Consistent with the findings of previous studies [36][37][38], peaks of coherence were observed in our results in the frequency band associated with Mayer waves (0.05-0.15 Hz) as shown in figures 6(b)-(e), potentially indicating the presence of spurious correlations in connectivity measures. Second, some form of normalization of coherence data is required as coherence measured in some infant participants could be slightly higher than their agematched peers due to inherent differences in brain structure and anatomy.…”
Section: Functional Connectivity Analysissupporting
confidence: 93%
“…First, this approach attempts to address the issue of spurious correlations in functional connectivity measures introduced by systemic physiological artifacts (particularly due to Mayer waves around 0.05-0.1 Hz). Consistent with the findings of previous studies [36][37][38], peaks of coherence were observed in our results in the frequency band associated with Mayer waves (0.05-0.15 Hz) as shown in figures 6(b)-(e), potentially indicating the presence of spurious correlations in connectivity measures. Second, some form of normalization of coherence data is required as coherence measured in some infant participants could be slightly higher than their agematched peers due to inherent differences in brain structure and anatomy.…”
Section: Functional Connectivity Analysissupporting
confidence: 93%
“…2021 ). It is reported only recently that RSFC can be quantified more accurately with a short S-D reading correction than without correction ( Paranawithana et al. 2022 ).…”
Section: Discussionmentioning
confidence: 99%
“…To remove such potential contamination, extra optical channels of fNIRS with a short source-detector (S-D) separation (commonly ∌0.8-1.2 cm) have been used for systemic noise removal in task-evoked hemodynamic studies (Zhang et al, 2007;Tian et al, 2011;YĂŒcel et al, 2015;Zhou et al, 2020;Noah et al, 2021), where a cortical region is functionally stimulated by a given task. However, most fNIRS-derived FC studies did not consider this confound effect until a recent report demonstrated that resting-state FC analysis with short S-D correction provides better accuracy than without correction (Paranawithana et al, 2022). We knowledge another weakness of this study is that the potential contribution from the extracranial layers to the hemodynamic results has not been considered.…”
Section: Potential Contamination Of Extracranial Layers To the Interp...mentioning
confidence: 96%